HUBUNGAN PENGETAHUAN PASIEN KANKER KOLON DENGAN TINGKAT KECEMASAN DALAM MENJALANI KEMOTERAPI DI RUANG RAWATAN INAP GB3A RUMAH SAKIT MURNI TEGUH - Lubis, Juwita; Hizkianta Sembiring (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Colorectal cancer is the growth of malignant cells in the body on the surface of the intestine, starting from the growth of non-malignant cells, commonly called abenomas, which in their early stages form polyps (cells that grow very quickly). Chemotherapy treatment is one way to do chemotherapy. This treatment can cause anxiety in patients who will undergo it. The purpose of this study was to determine the relationship between the knowledge of colon cancer patients and the level of anxiety in undergoing chemotherapy. This type of research uses correlation techniques (correlation study), with a total sample technique and the number of respondents is 64 respondents. data analysis using spearman test. The results of this study used the spearmen test and obtained the results. There is a significant relationship between knowledge of anxiety in patients undergoing chemotherapy in colon cancer patients in the Gb3a Inpatient Room, Murni Teguh Hospital, Medan, with the spearmen test results obtained 0.001 <0.005, meaning there is a significant relationship. to future researchers to make more samples and add other independent variables.